2010
DOI: 10.1117/12.853845
|View full text |Cite
|
Sign up to set email alerts
|

Group velocity control in multiple-beam and Mach-Zehnder interferometers

Abstract: In this work, we demonstrate the existence of abnormal pulse propagation regimes in linear and passive multiple-beam interferometers, where the group velocity can be tuned from subluminal to superluminal values by simply changing the length of one of the interferometer's arms. Experiments are performed in the radiofrequency range by using coaxial transmission lines. The interferometers group delay is characterized both in the frequency and in the time domain. Group velocities of 2c and tunnelling with negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Instead of connecting in series several MZIs, we increase the number of arms of a single interferometer. As a first attempt, we considered a four-beam interferometer with a nominal length difference ( ) between adjacent arms [28,29]. The system was built with coaxial cables and measurements were performed for narrowband RF pulses centered at the transmission minima (the system exhibits three minima between two main transmission peaks).…”
Section: Introductionmentioning
confidence: 99%
“…Instead of connecting in series several MZIs, we increase the number of arms of a single interferometer. As a first attempt, we considered a four-beam interferometer with a nominal length difference ( ) between adjacent arms [28,29]. The system was built with coaxial cables and measurements were performed for narrowband RF pulses centered at the transmission minima (the system exhibits three minima between two main transmission peaks).…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to PBG systems, we recently demonstrated that structural SFL can be generated in multiple-beam interferometers of three or more branches [25,26], which are linear and passive systems not exhibiting photonic band gaps. The simplest interferometer of this kind, with only two branches, is the Mach-Zehnder interferometer.…”
Section: Introductionmentioning
confidence: 99%